White lies and black markets : evading metropolitan authority in colonial Suriname, 1650-1800 - Fatah-Black, Karwan (Atlantic world (Leiden, Netherlands) ;, 2015)
"In White Lies and Black Markets, Fatah-Black offers a new account of the colonization of Suriname--one of the major European plantation colonies on the Guiana Coast--in the period between 1650-1800. While commonly portrayed as an isolated tropical outpost, this study places the colony in the context of its connections to the rest of the Atlantic world. These economic and migratory links assured the colony's survival, but also created many incentives to evade the mercantilistically inclined metropolitan authorities. By combining the available data on Dutch and North American shipping with accounts of major political and economic developments, the author uncovers a hitherto hidden world of illicit dealings, and convincingly argues that these illegal practices were essential to the development and survival of the colony, and woven into the fabric of the colonial project itself"--Provided by publisher